PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEGABAI VARIABEL INTERVENING PADA PENGGUNA OJEK ONLINE GRAB (STUDI PADA MAHASISWA STIE TAMANSISWA BANJARNEGARA) - Lustono Lustono (Medikonis, 2020)
ABSTRACT This study aims to determine the effect of service quality with price on customer loyalty through customer satisfaction as an intervening variable. STIE Tamansiswa Banjarnegara case study. In this study the independent variable consists of service quality and price, the intervening variable is customer satisfaction and the dependent variable is customer loyalty. The population of this study is 203 the total number of active students of STIE Tamansiswa Banjarnegara. While the sample of this study was 135 respondents. With accidental sampling technique. The type of research data is primer and data collection techniques using questionnaires. The results showed that partially the quality of service did not have a significant positive effect on customer loyalty. Price has a significant positive effect on customer loyalty. Service quality has a significant positive effect on customer satisfaction. Price has a significant positive effect on customer satisfaction. Customer satisfaction has a positive effect on customer loyalty. Customer satisfaction does not mediate the relationship between customer satisfaction and customer loyalty. Customer satisfaction can mediate a negative relationship between price and customer loyalty.